An improved energy management for MVDC distribution system based on exponential droop control - Lu, Wenbiao; Xiao, Qian; Jia, Hongjie; Mu, Yunfei; Cui, Mingjian; Jin, Yu; Li, Tianxiang; Zhang, Yuwei; Yu, Xiaodan (Frontiers in Energy Research, 2022)
The energy management optimization and DC voltage stability are the main challenges when loads surging and renewable energy sources (RESs) fluctuations occur in the medium-voltage DC distribution system (MVDC-DS). To solve these issues, this paper proposes a dual-time scale energy management method based on improved droop control for the MVDC-DS. Firstly, a ±10kV three-terminal hybrid modular multilevel converter (MMC)-based ring MVDC-DS with DC fault ride-through capability is constructed, which including electric vehicle charging stations, energy storage stations, multiple loads and RESs. Secondly, the droop control adopted by the hybrid MMC is improved by exp-function to achieve higher power quality. On this basis, a dual-time scale energy management method is proposed to minimize the electricity purchasing cost. The reference powers of each controllable unit are optimized in the long time-scale, and the parameters of improved droop control are optimized in the short time-scale. Finally, a case study is conducted on the ±10kV three-terminal hybrid MMC-based ring MVDC-DS, and the results indicate that the proposed method can improve the economy and power quality of system, and the exp-droop control can maintain the normal system operation under different conditions.